Vocabulary Building Strategies According to Learners’ Levels in Writing Skill (A field study on non-native Arabic learners in Bangladesh) - Bouanani, Mostafa; Ashrafuzzaman, Talha (LANGUAGE ART, 2021)
This study tries to discover the appropriate strategies for developing vocabulary size (word bank) in different levels of Arabic language learning, depending on three tests: Y/N (Yes or No test), MC (Multiple choice test), and writing skill test, that were given to a sample of non-native Arabic learners. The assumption of the study is that vocabulary building and learning strategies vary according to the target group of learners, i.e. whether they are native or non-native speakers of Arabic. The study aims to develop specific strategies for building corpora and word lists that help in curriculum design and evaluation. The results of the mentioned tests proved the strength of the relation between vocabulary size and writing skill as the former explains as much as 53% of the later. This means vocabulary size forms more than half of writing skill factors. Additionally, the process of discovering the details of the relation between the two gave us insights into the proper strategies for building and developing vocabulary size according to learners’ levels, indicating that frequency lists based on the lemma as a counting unit are more suitable for teaching and evaluation for learners from beginner and intermediate levels, while root-based frequency lists are more appropriate for advanced learners.